Eosinophils in Colorectal Neoplasms Associated with Expression of CCL11 and CCL24 - Hyuck Cho; Sung-Jig Lim; Kyu Yeoun Won; Go Eun Bae; Gou Young Kim; Ji Won Min; Byeong-joo Noh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: A decrease in the number of tissue eosinophils is known to reflect the malignancy potential of neoplastic lesions and even prognosis. Increased levels of the chemokines CCL11 and CCL24 in serum and tissue are also known to have diagnostic value as serum tumor markers or prognostic factors. The aim of this study was to evaluate the correlation between the degree of tissue eosinophilia and the expression of these chemokines in the glandular and stromal cells of colorectal neoplastic lesions ranging from benign to malignant tumors. Methods: We counted the number of infiltrating eosinophils in neoplastic lesion tissue and we evaluated the expression of CCL11 and CCL24 in glandular cells and stromal cells by immunohistochemical staining. Results: The results showed that the number of eosinophils decreased significantly and the expression of CCL11 and CCL24 in glandular cells decreased with tumor progression, whereas the stromal expression of CCL11 and CCL24 appeared to increase. Conclusions: The discrepancy in CCL11 and CCL24 expression between glandular cells and stromal cells might shed light on how colorectal cancer evades the immune system, which would enable further development of immunotherapies that target these chemokines. Further research on eosinophil biology and the expression pattern of chemokines in tumor cells is needed.